Characterization and Evaluation of Bambara Groundnut (Vigna subterranea (L.) Verdc.) for Yield and Related Traits in Asosa Zone, Northwestern Ethiopia - Mesay Paulos; Gobeze Loha; Mesfin Kassa (Applied and Environmental Soil Science)
Bambara groundnut, a future emerging legume, is usually known as a poor man’s crop or as “women’s crop” and newly noted as crop for new millennium. In this context, a field experiment was conducted during 2019/20 cropping season at Sonka testing site of Asosa zone in northwestern Ethiopia with objective to estimate the variability of Bambara groundnut genotypes with respect to important quantitative and qualitative traits. Treatments consisted in 20 accessions collected from five distracts of Benishangul Gumuz province in northwestern Ethiopia. The treatments were laid out in a randomized block design with three replications. All the qualitative characteristics recorded for genotypes showed different modalities and frequencies at vegetative stage with 70.12% of the fully expanded leaflet colour, 74.26% oval terminal leaflet shape, 76.24% petiole green colour, 78.22% stem green colour, 88.27% sparse hair on their stems, 70.41% spreading types, 81.33% rounded base with a point at the top, 90.11% yellowish brown pods at harvest, and 90.06% oval shaped seeds. With respect to quantitative traits, genotypes AMN/04/013, AMN/04/014, AMN/04/015, AMN/04/019, and AMN/04/020 gave relatively higher grain yield (>2000 kg/ha) with the highest grain yield recorded for genotype AMN/04/016. Thus, these genotypes showed relatively better adaptation at tested location. Higher correlation values were observed for days to maturity, plant height, number of stems per plant, pods per plant, seed per pod, and HSW, indicating that these traits are very important to be used in selection for the crop improvement. Agronomic and morphological evaluations have provided more accurate estimation of genetic diversity, the raw material of plant breeding. In general, this study enabled to determine how the influential traits direct to improve Bambara groundnut genotypes.